Responses of Pseudomonas aeruginosa to antimicrobials - Morita, Yuji; Tomida, Junko; Kawamura, Yoshiaki (Frontiers in Microbiology, 2014)
Infections caused by Pseudomonas aeruginosa often are hard to treat; inappropriate chemotherapy readily selects multidrug-resistant P. aeruginosa. This organism can be exposed to a wide range of concentrations of antimicrobials during treatment; learning more about the responses of P. aeruginosa to antimicrobials is therefore important. We review here responses of the bacterium P. aeruginosa upon exposure to antimicrobials at levels below the inhibitory concentration. Carbapenems (e.g., imipenem) have been shown to induce the formation of thicker and more robust biofilms, while fluoroquinolones (e.g., ciprofloxacin) and aminoglycosides (e.g., tobramycin) have been shown to induce biofilm formation. Ciprofloxacin also has been demonstrated to enhance the frequency of mutation to carbapenem resistance. Conversely, although macrolides (e.g., azithromycin) typically are not effective against P. aeruginosa because of the pseudomonal outer-membrane impermeability and efflux, macrolides do lead to a reduction in virulence factor production. Similarly, tetracycline is not very effective against this organism, but is known to induce the type-III secretion system and consequently enhance cytotoxicity of P. aeruginosa in vivo. Of special note are the effects of antibacterials and disinfectants on pseudomonal efflux systems. Sub-inhibitory concentrations of protein synthesis inhibitors (aminoglycosides, tetracycline, chloramphenicol, etc.) induce the MexXY multidrug efflux system. This response is known to be mediated by interference with the translation of the leader peptide PA5471.1, with consequent effects on expression of the PA5471 gene product. Additionally, induction of the MexCD-OprJ multidrug efflux system is observed upon exposure to sub-inhibitory concentrations of disinfectants such as chlorhexidine and benzalkonium. This response is known to be dependent upon the AlgU stress response factor. Altogether, these biological responses of P. aeruginosa provide useful clu